IDENTIFIKASI TUMBUHAN BAWAH DI OBYEK WISATA ALAM GOA JEPANG KALIURANG, SLEMAN, YOGYAKARTA - MAULANA, IMAM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Under vegetation is usually a kind of grass, herbs, bushs, or shrubs. This kind of vegetations are annual, biannual, or perennial with form as clumps, stands, spread,and climbs. Generally clans part of Araceae, Asteraceae, Cyperaceae,Poaceae, ferns, etc. These vegetations is usually founds on an open area, roadside, river bank, forest floor, agricultural land, and gardens. The community of vegetations is a group of vegetations organized by many kinds of vegetations which specially growth together at same place and that group has an interaction of each individual species with the environtment. This research was took place in natural touring object Goa Jepang, Kaliurang, Sleman, Yogyakarta. Sampling was placed in a right and left side of road crossingly. Measuring plot spacing from road is 2 meters and space between each measuring plot is 10 meters. There are 16 plots with size of 2x2 meters wich is in the nested sampling sized 20 x 20 meters. The results from this reaserch is there are 37 kind of under vegetations from 20 families. From that amount the most dominated family is from Poaceae with the relative density highly from Digitarialongifolia with value of20,633%, the lowest relative density is from Cissus sp.,Cratoxylon sp., Desmodiumtrifiorum, Eupatorium odoratum, Rubus sp.,and Saurauia bracteosa wth value 0,117%.